2021
DOI: 10.21203/rs.3.rs-901632/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Academic success online: The mediating role of self-efficacy on personality and academic performance

Abstract: Academic success in any context is dependent upon a student's belief in their ability to succeed. While learning online, a students’ self-efficacy is affected by their confidence in their ability to interact within the online environment. With the proliferation of personalized learning and the growth of Massive Open Online Courses, this growing trend is a shift in focus from the centralized brick-and-mortar locus of control, to one of enabling student choice and agency for how, when, and where they learn. In t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 52 publications
1
2
0
Order By: Relevance
“…A mediating role of self-efficacy on the relationship between BAS and sports success was fully confirmed in this study, consistent with hypothesis H4 and a previous study [ 2 , 36 , 37 , 38 , 39 , 40 , 41 , 42 , 43 , 44 , 45 , 46 , 47 , 48 , 49 , 50 , 51 , 52 , 53 ]. According to the RST [ 32 , 33 , 34 ], an approach and avoidance motivated behavior results from the interaction between neuropsychological personality traits and motivational stimuli that possess a specific value (more or less attractive).…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…A mediating role of self-efficacy on the relationship between BAS and sports success was fully confirmed in this study, consistent with hypothesis H4 and a previous study [ 2 , 36 , 37 , 38 , 39 , 40 , 41 , 42 , 43 , 44 , 45 , 46 , 47 , 48 , 49 , 50 , 51 , 52 , 53 ]. According to the RST [ 32 , 33 , 34 ], an approach and avoidance motivated behavior results from the interaction between neuropsychological personality traits and motivational stimuli that possess a specific value (more or less attractive).…”
Section: Discussionsupporting
confidence: 92%
“…Self-efficacy was found as a mediator in the relationships between the Big-Five personality traits and academic performance [ 50 , 51 ] and between a proactive personality and creative performance [ 52 ] and between goal setting and performance in the context of human resource management [ 53 ]. Furthermore, Sherman et al [ 49 ] found the mediating effect of flossing self-efficacy on the relationship between BIS/BAS motivational system, flossing intention, and health-related flossing behavior.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation